2015
DOI: 10.5717/jenb.2015.19.3.255
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a 12-week walking exercise program on body composition and immune cell count in patients with breast cancer who are undergoing chemotherapy

Abstract: Effect of a 12-week walking exercise program on body composition and immune cell count in patients with breast cancer who are undergoing chemotherapy. JENB., Vol. 19, No. 3, pp.255-262, 2015 [Purpose] The purpose of this study was to examine the effect of a 12-week walking exercise program on body composition and immune cell count in patients with breast cancer who are undergoing chemotherapy.[Methods] Twenty patients (age, 47.8 ± 3.12) participated in the study. Body composition (weight, body mass index, mus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 47 publications
1
4
0
Order By: Relevance
“…Leucocyte complexity indirectly provides insight into breast cancer survival [30] and can be modulated by exercise [31]. Our unchanged total leucocyte count during Intervention study and Follow-up was also observed in a study by Kim et al, where the effect of a 12-week walking exercise on the immune cells was examined [32] which is in accordance with our neopterin data. The experimental values in IG in leucocyte count was also accompanied by a significantly decreased and presumably beneficial hsCRP response.…”
Section: Discussionsupporting
confidence: 91%
“…Leucocyte complexity indirectly provides insight into breast cancer survival [30] and can be modulated by exercise [31]. Our unchanged total leucocyte count during Intervention study and Follow-up was also observed in a study by Kim et al, where the effect of a 12-week walking exercise on the immune cells was examined [32] which is in accordance with our neopterin data. The experimental values in IG in leucocyte count was also accompanied by a significantly decreased and presumably beneficial hsCRP response.…”
Section: Discussionsupporting
confidence: 91%
“…The exercise intensity in our study is substantially lower compared to the above-mentioned study, which might explain why we did not find significant change in CD14 + CD16 − monocytes and that the increase in CD14 + CD16 + monocytes was lower in our study (51% in our study versus 121% in Khosravi et al 15 . Moreover, it seems that chronic exercise does not change the immune cell counts in breast cancer patients 16 or survivors 15 . The mobilization induced by acute exercise appears to be transient, as also noticed in the present study.…”
Section: Discussionmentioning
confidence: 97%
“…However, it is widely accepted that findings in healthy individuals can not be generalized to diseased states, such as cancer. In breast cancer patients, the effect of exercise has been examined during and after cancer treatments 15 , 16 . However, to the best of our knowledge there are no studies investigating the effects of acute exercise on immune cell counts in breast cancer patients before the start of cancer treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding immune cell function, NK cell cytotoxicity was increased in two studies (86,109) and unchanged in two studies (96,115), lymphocyte proliferation was increased in two studies (86,90), and lymphocyte cytokine production was reported in four studies with mostly no change (83,86,90,105). When comparing post-PA intervention to pre-intervention, one study reported a reduction in the percentage of lymphocytes and monocytes and an increase in granulocytes (98), while two other studies reported no change in the percentage of T cells or NK cells (93,97). One study reported increased NK cell cytotoxicity post PA intervention (97).…”
Section: Clinical Findingsmentioning
confidence: 96%
“…Therefore, we classified the included studies into three categories: PA interventions given before, during, and after treatment. The existing evidence base only includes two pre-treatment (pre-surgical)(94,113) and eight duringtreatment(93,95,101,110,114,115,117,119) PA studies, while the majority of studies (n=27) assessed the effect of PA interventions post-cancer treatment.Most included studies assessed the effect of PA intervention on serum immune and inflammatory cytokines, the majority of which reported null results(83,85,(87)(88)(89)(90)(91)(92)94,99,100,102,103,105,108,110,(115)(116)(117)119). Several studies also compared post-PA intervention to pre-PA intervention serum cytokine levels, with mixed results showing either a reduction…”
mentioning
confidence: 99%